Effect of strategic leadership in promotion strategic practices of human resource management : An analytical and comparative survey of the opinions of a sample of administrative leaders at Imam Al-Sadiq University (Peace be upon Him) and Imam Al- Kadim College (Peace be upon Him) in Maysan Governorate - أحمد كاظم بريس; محمد علي حسين الساعدي (Iraqi Journal for Administrative Sciences, 2024)
The current research aims to test the impact of strategic leadership according to (Hitt at el, 2011) model in promoting strategic human resources practices. Sample of (91) employees working in (Imam Al-Sadiq University) and (Imam Al-Kadhim,) College in Maysan Governorate. Data was collect using a questionnaire. Statistical methods were used to analysis data such as simple correlation and regression. A Set of conclusions were reached the most prominent of which is that the interest of Imam Al-Sadiq University and Imam Al-Kadhim College are closely related to employment of individuals with competence and experience .A set of recommendations were reached the most prominent of which is should enhance the awareness of their affiliates of the meaning of the strategic direction in order to define the future vision and goals and formulate strategies and implement them.